A Cultural Approach to Evaluating Leadership Development. (February 2013) - Edwards, Gareth; Turnbull, Sharon
The Problem: Current thinking around the evaluation of leadership development programs pays insufficient attention to the way that learning to lead becomes embedded and affected by the cultural context within which leaders and leadership operate. The Solution: We propose an enhanced appreciation of cultural factors, organizationally, regionally, and nationally, when evaluating leadership development programs. We go on to suggest a cultural approach to the evaluation of such programs. This more cultural view enables a greater appreciation of current and contemporary accounts of leadership in the literature that are of a more distributed and cultural nature. This view also enables a more significant appreciation of shifting cultures, contexts, and situations within the process of learning that is a central element of leadership development. The Stakeholders: This article will appeal to researchers in the area of leadership and leadership development, as well as those engaged in the design, delivery, and evaluation of leadership development in a professional capacity.